2021
DOI: 10.1016/j.invent.2021.100442
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the web-based ‘Partner in Balance’ intervention to support spouses of persons with frontotemporal dementia

Abstract: Frontotemporal dementia (FTD) typically starts before the age of 65 years, and symptoms differ from other dementias (e.g. Alzheimer's dementia). Spouses are often caregiver and experience difficulty coping with the profound changes in personality and behavior accompanying FTD. Most interventions available to these spouses do not match their need for tailored and flexible psychosocial support. Therefore, tailored content for spouses of persons with FTD was recently incorporated in the proven effective and web-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…Interventions tended to be well-designed and easy to use [ 98 , 105 , 108 - 110 , 113 , 116 , 117 , 124 - 127 , 131 - 134 , 136 - 138 , 141 , 143 , 146 ]. There were mixed views on whether caregivers preferred dyadic or individual interventions [ 109 , 110 , 125 , 135 , 139 , 140 ]; however, there was generally a need for space to be created to allow caregivers to express themselves without the presence of care recipients [ 119 , 123 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions tended to be well-designed and easy to use [ 98 , 105 , 108 - 110 , 113 , 116 , 117 , 124 - 127 , 131 - 134 , 136 - 138 , 141 , 143 , 146 ]. There were mixed views on whether caregivers preferred dyadic or individual interventions [ 109 , 110 , 125 , 135 , 139 , 140 ]; however, there was generally a need for space to be created to allow caregivers to express themselves without the presence of care recipients [ 119 , 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interventions using different forms of media to deliver content [ 120 , 127 , 138 , 144 ] and supporting the use of interventions across devices (eg, ability to use intervention on a smartphone and computer) [ 132 , 144 ] made it easier for caregivers to use interventions. Tailored intervention content (eg, tailored to the care recipient’s stage of disease) [ 126 , 131 , 138 , 140 , 143 , 144 ], the provision of professional support [ 114 , 119 , 126 , 127 , 131 - 133 , 135 , 136 ,​ 138 - 141 , 143 , 144 ], a positive tone for information that was presented [ 125 , 127 , 138 , 140 ], and contact with information from other caregivers [ 114 , 120 , 126 , 127 , 131 , 132 , 136 , 138 - 140 ,​ 143 , 144 ] were important features to ensure interventions were relevant and met the needs of caregivers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, participants highlighted that it was pleasing to receive information tailored for different YOD-subtypes. Previous research has confirmed that caregivers have a need for YOD-subtype specific information ( Bannon et al, 2021 ; Bruinsma et al, 2021b ; Rosness et al, 2008 ). As known, support mainly focuses on Alzheimer's dementia or older peers ( Cations et al, 2017 ; Mayrhofer et al, 2018 ).…”
Section: Discussionmentioning
confidence: 94%
“…The RHAPSODY program could serve as a stepping stone for caregivers to participate in other support options. For example, in the Netherlands, tailored support is available that blends a web-based approach with personal coaching, namely the Partner in Balance intervention ( Bruinsma et al, 2021a ; Bruinsma et al, 2021b ). Lastly, although the current study showed good user acceptability, usability, and user satisfaction of the Dutch RHAPSODY program, a direction for future research would be to explore the long-term effects on caregiver well-being and coping skills.…”
Section: Discussionmentioning
confidence: 99%